Systematic survey of variants in TBX1 in non-syndromic tetralogy of Fallot identifies a novel 57 base pair deletion that reduces transcriptional activity but finds no evidence for association with common variants. Issue 20 (11th October 2010) - Griffin, Helen R; Töpf, Ana; Glen, Elise; Zweier, Christiane; Stuart, A Graham; Parsons, Jonathan; Peart, Ian; Deanfield, John; O'Sullivan, John; Rauch, Anita; Scambler, Peter; Burn, John; et al.
Abstract : Background: Tetralogy of Fallot (TOF) is common in individuals with hemizygous deletions of chromosome 22q11.2 that remove the cardiac transcription factor TBX1 . Objective: To assess the contribution of common and rare TBX1 genetic variants to TOF. Design: Rare TBX1 variants were sought by resequencing coding exons and splice-site boundaries. Common TBX1 variants were investigated by genotyping 20 haplotype-tagging SNPs capturing all the common variations present at the locus. Association analysis was performed using the program UNPHASED. Patients: TBX1 exons were sequenced in 93 patients with non-syndromic TOF. Single nucleotide polymorphism analysis was performed in 356 patients with TOF, their parents and healthy controls. Results: Three novel variants not present in 1000 chromosomes from healthy ethnically matched controls were identified. One of these variants, an in-frame 57 base-pair deletion in the third exon which removed 19 evolutionarily conserved residues, decreased transcriptional activity by 40% in a dual luciferase assay (p=0.008). Protein expression studies demonstrated that this mutation affected TBX1 protein stability. After correction for multiple comparisons, no significant associations between common genetic variants and TOF susceptibility were found. Conclusion: This study demonstrates that rare TBX1 variants with functional consequences are present in a small proportion of non-syndromic TOF.